2007
DOI: 10.1063/1.2722748
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of alkali metals with perylene-3,4,9,10-tetracarboxylic-dianhydride thin films studied by IR spectroscopy

Abstract: In order to clarify the doping behavior of different alkali metals in perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA), Fourier transform infrared spectra of PTCDA thin films doped with sodium, potassium, and cesium were measured and compared. Furthermore the vibrational properties were calculated using density-functional theory and these calculated vibrational frequencies were assigned to the experimental IR modes of the thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Upon closer inspection, the potassium atoms are located near the oxygen atoms and exhibit rather similar bonding distances to PTCDA as compared to the calculated structure of free-standing K 2 PTCDA complexes. 10 It has been shown that such a structure is a consequence of an ionic bonding between the alkali metal and PTCDA resulting in PTCDA dianion formation. 8,11 By inspecting domains of the K 2 PTCDA phase (cf.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon closer inspection, the potassium atoms are located near the oxygen atoms and exhibit rather similar bonding distances to PTCDA as compared to the calculated structure of free-standing K 2 PTCDA complexes. 10 It has been shown that such a structure is a consequence of an ionic bonding between the alkali metal and PTCDA resulting in PTCDA dianion formation. 8,11 By inspecting domains of the K 2 PTCDA phase (cf.…”
Section: Resultsmentioning
confidence: 99%
“…128-69-8) intercalated with potassium . Since then, the interaction of PTCDA with alkali metal atoms has attracted considerable attention, particularly with regard to electronic and optical properties. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Doping was performed by subsequent evaporation of the alkali metal from a dispenser source ͑SAES Getters, Italy͒ on top of the PTCDA films. Because alkali metals brought into a PTCDA layer by this technique are known to establish a highly doped surface layer, probably with a diffusion profile into the bulk, 9,19 the freshly doped layers were annealed at 360 K for 12 h, in order to obtain homogeneous amalgamation.…”
Section: A Sample Preparationmentioning
confidence: 99%
“…Instead, at room temperature initially a highly doped surface layer is built, probably with a diffusion profile into the bulk. By means of IR spectroscopy it was shown 19 that the diffusion and reaction of freshly deposited dopant with undoped PTCDA molecules persists over hours. In order to ensure maximum equilibration of dopant within the PTCDA layer all investigated samples were annealed in UHV for about 1 h. As recently reported results 9 indicate that annealing temperatures above 390 K lead to fundamental changes in alkali metal doped PTCDA layers, e.g., a decrease of conductivity, the presented measurements were performed on samples annealed at about 360 K.…”
Section: B Sodium Doped Ptcdamentioning
confidence: 99%